Design and Development of Modified Hybrid Resonant Converter with Valley-fill for LED Lighting - BALAKRISHNAN, L. P.; RAMALINGAM, S. (Advances in Electrical and Computer Engineering, 2023)
LED (light-emitting diode) drivers with the non-resonant DC-DC converters produce higher current and voltage ripple than the resonant converters. The resonant converter-based LED drivers provide low cost, high efficiency, enhanced soft switching capabilities, and simple construction. Therefore, this research work is motivated to propose a hybrid resonant converter to power the LED. The proposed modified hybrid resonant with valley-fill converter is built by removing the capacitors across the switches and the output diode is replaced with a valley-fill circuit in the conventional hybrid resonant converter. With the valley-fill circuit, the switches and the diode are subjected to reduced stress, reduced flicker, and improved efficiency. The modified Hybrid resonant converter with valley-fill circuit LED driver’s performance parameters are compared with existing resonant converter topologies in terms of component count, current stress, voltage stress across the switch and output diode, LED voltage ripple, current ripple, and efficiency. A 10 W, 24 V laboratory prototype of modified Hybrid resonant converter with valley-fill circuit LED driver is developed, and the simulation results are validated.